2020
DOI: 10.3390/en13215640
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of a Composite Solar Wall Integrating a PCM in a Individual House: Heating Demand and Thermal Comfort Considerations

Abstract: Thermal energy storage (TES), which features an innovative technology, can enhance energy efficiency in the building sector and reduce CO2 emissions. Due to their high heat storage capacity, phase change materials (PCMs) have impressed many researchers. This paper investigates the energy performance of an individual house integrating a solar Trombe wall containing PCM with respect to heating demand and thermal comfort applications. The thermal energy performance of the design house was simulated using Dymola/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This is accomplished by preserving and protecting the natural resources around the project site. Since it is not practical to experimentally measure the thermal properties of all the components and construction systems, it is advisable to use advanced and accurate methods to reliably predict their thermal performance [3]. From reducing carbon footprints by using renewable energy, using on-site water treatment plants to minimize waste, to recycling and building with renewable or waste materials, like bricks, there are still many ways in which sustainability of the building construction can be improved [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by preserving and protecting the natural resources around the project site. Since it is not practical to experimentally measure the thermal properties of all the components and construction systems, it is advisable to use advanced and accurate methods to reliably predict their thermal performance [3]. From reducing carbon footprints by using renewable energy, using on-site water treatment plants to minimize waste, to recycling and building with renewable or waste materials, like bricks, there are still many ways in which sustainability of the building construction can be improved [4].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of phase change material into the masonry elements significantly reduced temperature fluctuations on the inner surface of the tested barrier. In articles [27,28], phase change material in the form of microcapsules was incorporated into the structure of the cement mortar layer. Additionally, behind the accumulation layer and the air gap layer, an insulating layer with ventilation openings was placed.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a phase change material, its parameters play an important role. The higher the latent heat of the PCM, the lower the demand for thermal energy and, at the same time, the better the thermal comfort in the room [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nems and Puertas [23] experimentally studied a dual PCM for heat storage, they made a I-D model for dual PCM and validated their results using experimental results. Leang et al [24] performed design and optimization of composite walls by integrating a PCM in their design. Their study concluded that the higher the latent heat, the lower the heating demand and greater the thermal comfort of the interior of the house.…”
Section: Introductionmentioning
confidence: 99%